AUTOMATED RECOGNITION OF PROPER NOUNS IN NER OBJECTS (ANTHROPONYMS) - Madina T. Samatboyeva (Journals Park Publishing, 2024)
This article discusses proper nouns, their classification, their study within the field of onomastics, and the onomastic layer. Proper nouns differ significantly from common nouns due to their distinctive characteristics. Proper nouns can be categorized into various types, and even within major types, they can be classified into smaller subgroups based on the reasons for their naming. Anthroponyms (personal names) make up the largest category of proper nouns. The article specifically focuses on the identification of proper nouns, particularly anthroponyms, as part of NER (Named Entity Recognition) objects.
Keywords: proper nouns, common nouns, onomastics, NER, named entities, anthroponyms.